THE PROMOTION OF WRITING SKILLS IN ESL CLASSROOM - Yaxshiboyeva, Nargiza (Журнал иностранных языков и лингвистики, 2021)
Language is a tool of communication to express one’s ideas, thoughts, feelings and emotions. Hence, language, communication and speech are the three main important and essential tools that are useful in sharing our ideas with others. Humans have to acquire the skills of a particular language in order to communicate well with their fellow human beings. In the case of English also, humans should learn all the four language skills, i.e., listening, speaking, reading and writing. Once the learners of English get a good command over these skills, they can communicate well in English.